High frequency data and a weekly economic index during the pandemic - Daniel J. Lewis; Karel Mertens; James H. Stock; Mihir Trivedi (Federal Reserve Bank of New York, 2020)
This paper describes a weekly economic index (WEI) developed to track the rapid economic developments associated with the onset of and policy response to the novel coronavirus in the United States. The WEI, with its ten component series, tracks the overall economy. Comparing the contributions of the WEI's components in the 2008 and 2020 recessions reveals differences in how the two events played out at a high frequency. During the 2020 collapse and recovery, it provides a benchmark to interpret similarities and differences of novel indicators with shorter samples and/or nonstationary coverage, such as mobility indexes or credit card spending.
Keywords: E01; E66; C51; 330; weekly economic index; high frequency; measurement of economic activity; forecasting